2013
DOI: 10.1080/15538605.2013.785468
|View full text |Cite
|
Sign up to set email alerts
|

Counseling and Advocacy with LGBT International Students

Abstract: LGBT international students have unique issues and needs in coping with their student life in the United States. Their primary issues include developing their own sexual identity, coming out in a variety of academic and social settings, forming relationships, returning to home countries, and differing health-related issues from domestic students. Therefore, mental health professionals must be aware of these issues, provide support that fits the person's individual needs, and serve as advocates for these studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…Oba's and Pope's (2013) article and Pope et al's (2007) book chapter on counseling LGBQ international students, can serve as a foundation for mental health professionals to better understand the intersection of sexual orientation and international student status. Further, Pope and colleagues (2007) discuss the importance of mental health professionals reflecting about their personal biases to ensure that they are providing services that meet the individual needs of these students.…”
Section: Suggestions For Mental Health Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oba's and Pope's (2013) article and Pope et al's (2007) book chapter on counseling LGBQ international students, can serve as a foundation for mental health professionals to better understand the intersection of sexual orientation and international student status. Further, Pope and colleagues (2007) discuss the importance of mental health professionals reflecting about their personal biases to ensure that they are providing services that meet the individual needs of these students.…”
Section: Suggestions For Mental Health Professionalsmentioning
confidence: 99%
“…Further, Pope and colleagues (2007) discuss the importance of mental health professionals reflecting about their personal biases to ensure that they are providing services that meet the individual needs of these students. Practitioners can also provide resources and serve as advocates for this community (Oba & Pope, 2013). In addition, we suggest mental health professionals explore the LGBQ international student's relationships with peers, friends, family, and educators, as it relates to their overall experience.…”
Section: Suggestions For Mental Health Professionalsmentioning
confidence: 99%
“…One of the efforts that can be done is by improving students' understanding of their religion, experience, health, and sexual identity, how students view themselves (Allen & Jr., 2004, Dacholfany&Khoirurrijal, 2016Harper et al, 2013;Oba & Pope, 2013). By increasing students' understanding of their sexual identity, it is expected to prevent students from LGBT, such as by applying the "portfolio-based learning" or "portfolio-based learning" and "portfolioassists assessment" models (Sulaiman, Hasan, &Maksum, 2017), religious psychotherapy approach (Pasilaputra, 2016).…”
Section: Proceedings | International Conferences On Education Socialmentioning
confidence: 99%
“…However, among the participants of different nationalities and ethnicities, the international women residing in the U.S. were categorized as Asian American due to their status of residing in the U.S., in this study, which risked neglecting the distinct acculturation and enculturation experiences of the sojourning individuals. Oba and Pope (2013) identified that the four major challenges for international sexual minority students in the U.S. as facing issues related to identity disclosure, negotiating friendship and forming intimate relationships, navigating sexual health, and readjustment process when they plan to return home. They provided a helpful framework for mental health professionals to increase understanding of issues that pertain to international sexual minority students' experienced, and to provide support that may fit the needs from their intersecting identities.…”
Section: Sexual Orientation Identity Conceptualizations For Asian Intmentioning
confidence: 99%
“…Limited understanding has been established on the impact of dual cultural exposures and the multiple marginalized identities may have on their sexual identity development for international SOM students (Kato, 1998;Oba & Pope, 2013), particularly those who are women from countries with Chinese cultural heritages (Quach et al, 2013). Among SOM women of Chinese cultural heritages, internalized heterosexism often is the norm rather than the exception for these women, due to the Confucian expectations for women to fulfill their relational roles revolving patriarchal family structures (Chow & Cheng, 2010).…”
Section: Introductionmentioning
confidence: 99%